Efeito do fogo na dinâmica da vegetação arbórea de floresta manejada e não manejada na Flona do Tapajós, Pará, Brasil - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2020)
Among the disturbances of anthropic origin that occur in tropical forests, fire and its long-term impacts are still poorly known, especially when there are interactions with selective logging. With the monitoring of permanent plots, it is possible to describe the recovery trajectory and better understand the resilience mechanisms of the forest after the occurrence of fires. The objective of my thesis was to answer the following question: how does fire affect the recovery trajectory of a mature forest subjected to selective logging in the Brazilian Amazon? To tackle this question, it was used a set of 60 plots of 0.25 ha (50 m x 50 m; 12 sample hectares) installed in the Tapajós National Forest on 180 hectares of a mature terra firme forest with a history of forest management (1982) and fire (1997), monitored through frequent measurements of trees with DBH ≥ 5 cm, from 1981 to 2012 (31 years). To determine the disturbance effects, basal area, mortality rates, recruitment rates, and species diversity, were compared through Repeated Measures Variance Analysis (ANOVA) and Linear Mixed Effect Models (MLM). The results show that in the Brazilian Amazon, in the time of 15 years after the fire, Dense Ombrophilous Forest, is able to stabilize its mortality rates and forest structure remains similar to its original conditions, mostly due to mortality is concentrated among small trees (DBH < 20 cm), although there are still high recruitment rates and the strong presence of pioneer tree species. In managed forests affected by fire, logging intensity is a determining factor in the dynamics of tree vegetation, and therefore the resilience of the forest is directly associated with previous conditions of forest structure (basal area and presence of large trees). The combination of reduced impact logging, reduction of basal area of non-commercial species, and small fires did not cause losses in species diversity, although heavy thinning alters the species composition. In short, forests with no history of frequent disturbances are more fire resistant and resilient.
Keywords: Diversidade de espécie; Taxa de recrutamento; Taxa de mortalidade; IMPACTOS AMBIENTAIS E SOCIAIS DA MUDANÇA DO USO DA TERRA NA AMAZÔNIA; SOCIEDADE, NATUREZA E DESENVOLVIMENTO